Surgical treatment of patients with abdominal sepsis taking into account the prediction of the implementation of re-operations - I. A. Kryvoruchko; M. S. Antonova; O. V. Yevtushenko; S. A. Andreieshchev (Клінічна хірургія, 2020)
Objective. The investigation objective was improvement of the surgical treatment results in patients, suffering аbdominal sepsis, using individualized tactics of treatment, taking into account a possibility for the postoperative complications occurrence and the treatment results prognostication.